2022
DOI: 10.1007/s00705-022-05609-1
|View full text |Cite
|
Sign up to set email alerts
|

SARS CoV-2 infections in animals, two years into the pandemic

Abstract: In December 2019, several cases of pneumonia caused by a novel coronavirus, later identified as SARS-CoV-2, were detected in the Chinese city of Wuhan. Due to its rapid worldwide spread, on 11 March 2020 the World Health Organization declared a pandemic state. Since this new virus is genetically similar to the coronaviruses of bats, SARS-CoV-2 was hypothesized to have a zoonotic origin. Within a year of the appearance of SARS-CoV-2, several cases of infection were also reported in animals, suggesting human-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 121 publications
1
18
0
1
Order By: Relevance
“…There is now clear evidence that SARS-CoV-2 can move from humans to multiple other animal species (1). This is especially true for white-tailed deer (Odocoileus virginianus) and possibly other cervid species in North America, where early research found 40% of white-tailed deer had been exposed to SARS-CoV-2 (2) and more than one-third of deer in some populations were positive by rRT-PCR (real-time PCR with reverse transcription) (3).…”
Section: Main Textmentioning
confidence: 99%
“…There is now clear evidence that SARS-CoV-2 can move from humans to multiple other animal species (1). This is especially true for white-tailed deer (Odocoileus virginianus) and possibly other cervid species in North America, where early research found 40% of white-tailed deer had been exposed to SARS-CoV-2 (2) and more than one-third of deer in some populations were positive by rRT-PCR (real-time PCR with reverse transcription) (3).…”
Section: Main Textmentioning
confidence: 99%
“…Coronavirus has been found in many animal organisms, which indicates the early occurrence of their protective methods to fight this pathogen [54][55][56]. It is obvious that the low mortality of animal organisms is due to the creation in the process of evolution of endogenous substances that prevent high lethality from coronavirus.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus has been found in many animal organisms, which indicates the early occurrence of their protective methods to fight this pathogen [ 56 , 57 , 58 ]. It is obvious that the low mortality of animal organisms is due to the creation in the process of evolution of endogenous substances that prevent high lethality from coronaviruses.…”
Section: Discussionmentioning
confidence: 99%